HALAL INDUSTRY: OPPORTUNITIES AND CHALLENGE IN THE GLOBAL MARKET - Prayuda, Deni; Arby, Safardilah; Adli, Ihsanul; Al-Ayubi, Solahuddin (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This research aims to provide a deeper and more detailed understanding of the opportunities and challenges of the halal industry in the global market. The studyemploys qualitative analysis of secondary data, specifically metadata from 79 publications obtained from the Dimensions.AI database. The data is then processedusing Nvivo 12 Plus software, which facilitates a more systematic and structured data analysis. The findings of the research indicate that there are significant opportunities for the development of the halal industry, which continues to grow in the global market, particularly in the food and tourism sectors. However, there are several challenges in the development of the halal industry, including the lack of globally agreed-upon halal certification, supply chain issues, low awareness and understanding of halal products among the general public, and a shortage of halal product manufacturers. To address these challenges and strengthen the position of the halal industry in the global market, efforts to improve marketing strategies, foster innovation, and enhance understanding of halal products are necessary. Consequently, the results of this research have the potential to influence the global market by contributing to the future development of the halal industry.